Intelligent Identification and Construction System of Prefabricated Tunnel Structure Based on BIM Technology - Wenzhi Liu (Advances in Multimedia)
In order to make up for the problems of low production efficiency, high labor cost, serious environmental pollution, and low degree of informatization of traditional tunnel construction method, an intelligent identification building system of prefabricated tunnel structure is proposed. Based on BIM Technology and integrating advanced concepts and technologies in the construction industry and management field, an intelligent construction system of prefabricated tunnel structure based on BIM is proposed, the characteristics, functions, and values of each component are introduced, and the overall architecture of the system is established, which can provide technical support for the whole life cycle construction, operation, and maintenance of prefabricated railway tunnel. Only 68% of architectural designers know BIM Technology, while only 4% of designers really use or are using BIM Technology to participate in prefabricated architectural design. Through this research, the use frequency of BIM can be greatly increased and work efficiency can be improved. To meet the requirements of railway tunnel construction for intelligent construction in the new era, the new technology and new ideas also lead the further scientific and technological innovation in tunnel engineering to a certain extent, which meets the actual needs of the development of intelligent railway construction technology and has a practical significance of improving quality and efficiency.